PENGARUH PENGGUNAAN TEKNIK MIND MAPPING TERHADAP KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 3 BATUSANGKAR - Delia Putri (JURNAL PENDIDIKAN ROKANIA, 2016)
This article was written to look at the effect of using mind mapping techniques in the learning skills of writing news student class VIII SMP Negeri 3 Batusangkar. The data in this study is the result of student’s writing news. The data collection is done by collecting the news writing students before and after using mind mapping techniques. Hypothesis was tested by t-test formula. The result of this study as follow (1) result of the student news writing skills pretest experimental class is 60,76; (2) result of the student news writing skills posttest experimental class is 85,03; (3) Based on the result of ttest concluded that there is significant influence the use of mind mapping techniques in learning news writing class VIII SMP Negeri 3 Batusangkar